Erratum: Coffee Supply Chain Performance Measurement In Ulu Belu District, Tanggamus Regency, Lampung Province - Teny Sylvia; Teguh Wiyono; Endo Pebri Dani Putra; Muhammad Asrol; Noveliska Br Sembiring; Eka Nur'azmi Yunira; Deni Subara; Wilda Harlia Devita (Agroindustrial Journal, 2026)
This Erratum relates to the following article:Sylvia, T., Wiyono, T., Putra, E.P.D., Asrol, M., Sembiring, N.B., Yunira, E.N., Subara, D., Devita, W.H., 2025. Coffee Supply Chain Performance Measurement in Ulu Belu District, Tanggamus Regency, Lampung Province. Agroindustrial Journal 12(1), 27–42. https://doi.org/10.22146/aij.v12i1.106071The publisher regrets that, due to a production error, the publication metadata on page 1 of the published PDF version of the article (DOI: 10.22146/aij.v12i1.106071) contained incorrect dates. The incorrect information appeared as: “Received: June-04-2025; Accepted: June-25-2025; Published: June-30-2025”. The correct dates are: “Received: April 17, 2025; Accepted: June 25, 2025; Published: June 30, 2025”.The editorial office regrets the error.